SysGRID: IEC 61850 and IEC 61499 Standard Based Engineering Tool for Smart Grid Automation Design - Yang, Chen-Wei; Zhabelova, Gulnara; Vyatkin, Valeriy (EAI Endorsed Transactions on Energy Web, 2014)
The so called Smart Grid is said to be distributed in nature with an accompanying control architecture which is made up of a heterogeneous network of controllers communicating in a peer-to-peer manner. The paper proposes a novel computer-aided model-based system engineering process for the design of a Smart Grid applications from the initial design specification through to the validation of the control system and hardware deployment. The process is supported by the SysGRID tool, which plays the roles of a system configurator and device configurator adopted from the International Standard IEC 61850. SysGRID supports system-level design of automation logic in the form of function block networks compliant with the international standard IEC 61499. The capabilities of SysGRID are demonstrated through the process of designing a distributed protection application based on IEC 61850 and the resultant validation process in a close-loop co-simulation.
Keywords: IEC 61850; IEC 61499; SysGRID; SCL; Model-Based System Engineering; Sympathetic Tripping